2019
DOI: 10.1038/s41598-019-41626-y
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Differentiation of Breast Cancer Sub-Types using a cPLA2α Activatable Fluorophore

Abstract: Cytosolic phospholipase A2α (cPLA2α) has been shown to be elevated in breast cancer and is a potential biomarker in the differentiation of molecular sub-types. Using a cPLA2α activatable fluorophore, DDAO arachidonate, we explore its ability to function as a contrast agent in fluorescence-guided surgery. In cell lines ranging in cPLA2α expression and representing varying breast cancer sub-types, we show DDAO arachidonate activates with a high correlation to cPLA2α expression level. Using a control probe, DDAO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 54 publications
1
16
0
Order By: Relevance
“…The authors of the present review hypothesized that tumor tissues overexpress THSd7a, or Pla2r is expressed in neutrophils and lung cells, which leads to complement system activation and Mac formation (92,93,98). However, the current models do not help us answer the question of antigen production.…”
Section: Pathogenesis Of Imn: From Model To Humanmentioning
confidence: 77%
“…The authors of the present review hypothesized that tumor tissues overexpress THSd7a, or Pla2r is expressed in neutrophils and lung cells, which leads to complement system activation and Mac formation (92,93,98). However, the current models do not help us answer the question of antigen production.…”
Section: Pathogenesis Of Imn: From Model To Humanmentioning
confidence: 77%
“…This would reduce the time course of therapy to which patients are currently submitted. A similar approach could also reduce the dosage of chemotherapeutic agents required for the treatment of aggressive types of tumors, including those that present with high metastasis and relapsing rates, such as breast cancer [77][78][79] . Finally, further work will be required to address the potential role of Ambrisentan in the treatment of cancer and to better understand the mechanisms how this drug reduces metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies had shown that arachidonic acid esterified to visible fluorophores such as 7‐hydroxycoumarin were highly specific for cPLA2 and displayed hydrolysis kinetics similar to those of native substrates . We adapted this caged fluorescence protocol using fluorophores that emit in the red wavelength range (660–680 nm) to create cPLA2 sensitive probes suitable for in vivo imaging . Probe selectivity could be modulated by choice of fatty acids and fluorophores, with DDAO 6,8‐dichloro‐7‐hydoxy‐9,9‐dimethylacridin‐2( 9H )‐one arachidonate performing the best in vitro, in cells, and in tumors.…”
Section: Imaging Metabolic Lipid Changesmentioning
confidence: 99%